Optimized antimicrobial and antiproliferative activities of titanate nanofibers containing silver - Su YH (Dove Medical Press, 2011)
Yong Hua Su*, Zi Fei Yin*, Hai Liang Xin, Hui Qing Zhang, Jia Yu Sheng, Yan Long Yang, Juan Du, Chang Quan LingDepartment of Traditional Chinese Medicine, Changhai Hospital, The Second Military Medical University, Shanghai, People’s Republic of China*These authors contributed equallyAbstract: Titanate nanofibers containing silver have been demonstrated through the experiments reported herein to have effective antifungal and antiproliferative activities in the presence of UV light. The titanate nanofibers containing silver can be fabricated by means of ion exchange followed by a topochemical process in an environment suitable for reductive reactions. Excellent antibacterial, antifungal, and antiproliferative activities could be demonstrated by both Ag2Ti5O11 · xH2O and Ag/titanate (UV light irradiation) due to their unique structures and compositions, which have photocatalytic activities to generate reactive oxygen species and capabilities to continuously release the silver ions. Therefore these materials have the potential to produce a membrane for the treatment of superficial malignant tumor, esophageal cancer, or cervical carcinoma. They may also hold utility if incorporated into a coating on stents in moderate and advanced stage esophageal carcinoma or for endoscopic retrograde biliary drainage. These approaches may significantly reduce infections, inhibit tumor growth, and importantly, improve quality of life and prolong survival time for patients with tumors.Keywords: silver, titanate, photocatalytic, antiproliferative, antimicrobial